2013
DOI: 10.1086/670998
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Colonization and Infection with Methicillin-ResistantStaphylococcus aureusand Vancomycin-ResistantEnterococcusand ofClostridium difficileInfection in Canadian Hospitals

Abstract: These data provide the first national prevalence estimates for MRSA, VRE, and CDI in Canadian hospitals. Certain infection prevention and control policies were found to be associated with prevalence and deserve further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 34 publications
6
17
1
1
Order By: Relevance
“…The observation that all MRSA isolates were susceptible to linezolid is similar to reports from other countries that MRSA isolates were susceptible to linezolid [20,22,25] . In addition, the MIC distribution of the glycopeptide antibiotics showed that the majority ( ∼ 97%) of the isolates were susceptible to vancomycin and teicoplanin (MIC: ≤ 2 μg/ml), confirming that vancomycin and teicoplanin remain viable options for treating MRSA infections in Kuwait.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The observation that all MRSA isolates were susceptible to linezolid is similar to reports from other countries that MRSA isolates were susceptible to linezolid [20,22,25] . In addition, the MIC distribution of the glycopeptide antibiotics showed that the majority ( ∼ 97%) of the isolates were susceptible to vancomycin and teicoplanin (MIC: ≤ 2 μg/ml), confirming that vancomycin and teicoplanin remain viable options for treating MRSA infections in Kuwait.…”
Section: Discussionsupporting
confidence: 88%
“…The majority (40.9%) of the isolates in this study originated from skin and soft tissue infections concurring with the findings of a previously published study [22] . The results also mimicked the findings of a surveillance study conducted in 2005 in Kuwait hospitals [23] and two studies conducted in the USA and Canada [20,24] where skin and soft tissues were the major sources of MRSA isolates. In contrast to the findings of this study, lower respiratory tract samples were the major sources accounting for 40.6% of MRSA isolates obtained during an Italian national survey conducted in 2012 [25] .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The method used for the detection of C difficile is a major factor in the detection of CDI, and in the declaration and end of outbreaks. Improved diagnostic methods and a robust antibiotic stewardship program, 6 in addition to infection control policies and practices, environmental cleaning, 7 improving hand hygiene practices, 8 hospital design, 9 and better identification of asymptomatic carriers 10 should all result in better control of CDI.…”
Section: Discussionmentioning
confidence: 99%
“…Although providing important incidence data, the surveillance is limited in that only a relatively small number of hospitals, predominantly tertiary-care teaching facilities participate. In 2010 we conducted the first national prevalence survey of AROs, including methicillin-resistant Staphylococcus aureus (MRSA), vancomycinresistant Enterococcus (VRE), and Clostridium difficile infection (CDI), in a large and representative sample of Canadian hospitals [5]. However, as the epidemiology of these organisms continues to evolve it is important to monitor changes that may occur over time.…”
Section: Introductionmentioning
confidence: 99%